2013
DOI: 10.1186/cc13158
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative acute kidney injury and five-year risk of death, myocardial infarction, and stroke among elective cardiac surgical patients: a cohort study

Abstract: IntroductionThe prognostic impact of acute kidney injury (AKI) on long-term clinical outcomes remains controversial. We examined the five-year risk of death, myocardial infarction, and stroke after elective cardiac surgery complicated by AKI.MethodsWe conducted a cohort study among adult elective cardiac surgical patients without severe chronic kidney disease and/or previous heart or renal transplant surgery using data from population-based registries. AKI was defined by the Acute Kidney Injury Network (AKIN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 28 publications
4
66
0
1
Order By: Relevance
“…We excluded 268 studies: animal studies (15), reviews (42), no epidemiological data available (177), not about CRS-1 (23), no data about AKI or WRF (8) and studies evaluating a specific intervention (3). Finally, we included 64 papers (n = 509,766 patients), containing data on AKI in AHF patients (18 studies; 29,202 patients) [4,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26], ACS (15 studies; 282,113 patients) [13,27,28,29,30,31,32,33,34,35,36,37,38,39,40] and CS (32 studies; 198,451 patients) [41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72] (table 1). One study contained information about AHF as well as ACS and is therefore used in both groups [13].…”
Section: Resultsmentioning
confidence: 99%
“…We excluded 268 studies: animal studies (15), reviews (42), no epidemiological data available (177), not about CRS-1 (23), no data about AKI or WRF (8) and studies evaluating a specific intervention (3). Finally, we included 64 papers (n = 509,766 patients), containing data on AKI in AHF patients (18 studies; 29,202 patients) [4,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26], ACS (15 studies; 282,113 patients) [13,27,28,29,30,31,32,33,34,35,36,37,38,39,40] and CS (32 studies; 198,451 patients) [41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72] (table 1). One study contained information about AHF as well as ACS and is therefore used in both groups [13].…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis confirmed that patients who required dialysis for AKI post-operatively had greater early mortality [7]. Although some studies have examined long-term mortality and cardiovascular outcomes in survivors of severe AKI after cardiac surgery [6,11,12,13], few have evaluated the long-term renal outcomes and prognostic factors for chronic kidney disease (CKD) [4]. A systematic review of studies published between 2004 and 2014 by Pickering et al [7] using consensus definitions for AKI did not find any studies that reported associations between bypass-associated AKI and CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with severe or multi-vessel coronary artery disease, coronary artery bypass graft (CABG) improves survival compared to medical revascularisation [2]. However, acute kidney injury (AKI) is common after cardiac surgery, ranging from 10 to 60% depending on the definition used [3,4,5,6,7,8]. AKI was associated with greater short-term mortality such that up to 40-60% of patients with severe AKI died during the hospitalisation [3,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Post-operative AKI has important implications relating to subsequent mortality, morbidity, and cost. 4,[6][7][8] Endovascular techniques have evolved greatly since their conception and are now widely applied for the correction of atheromatous and non-atheromatous lesions in various vascular beds. Recently, technological evolutions have allowed the treatment of more complex pathologies using such techniques.…”
Section: Introductionmentioning
confidence: 99%